Holistic family herbal the natural way to improve your family's health - Campion, Kitty (Bloomsbury, 1997)
This health guide contains everything needed to know to treat family health, without recourse to conventional medicine. It describes the best ways of maintaining good health by harnessing the healing tools of the environment and following a corrective diet, and alerts the reader to the pitfalls of polluted water, air and soil. The book shows the natural way of dealing with over 200 common illnesses and problems, ranging from earache, bruises, childhood diseases and hypoglycaemia, listed alphabetically for easy access. It offers practical advice for solving health problems, supported by formulae for a wide range of herbal remedies which have been extensively tried and tested in the busy clinic the author has run for 15 years. A comprehensive directory on herbal medicine and naturopathy is included.